Gegar Budaya Ditinjau dari Dukungan Sosial pada Mahasiswa Thailand Selatan (Patani) - Irfani Rizal; Icha Herawati (Islamic Psychology Department, Dakwah Faculty of Universitas Islam Tribakti Lirboyo Kediri, 2020)
Cultural differences experienced by Thailand Selatan (Patani) students with Indonesian culture can cause cultural shock to Patani students. Culture shock is a reaction of individual discomfort when entering a new environment. One of the strategies in reducing culture shock is to get social support. This research examines whether there is a correlation between social support and culture shock in Patani students at the Islamic University of Riau. The research method used is quantitative research. Data collection was carried out using a scale of culture shock and social support scale. Pearson product-moment analysis was used to test the proposed hypothesis. Participants numbered 52 people using saturated sample techniques. The results showed that a negative and significant relationship between social support and culture shock in Patani students at the Islamic University of Riau with the r = -0,276 with p 0,024 (p< 0,05). The conclusion from this study shows that the higher the social support, the lower the culture shock. The culture shock was predicted by social support of 7.6%.